Revisited the conventional manoeuver of Hippocrates in method in temporal-mandible joint dislocation - Munjal, Manish; Munjal, Shubham; Arora, Vineeta; Jindal, Jyoti; Chauhan, Swati; Bansal, Garima; Mathur, Kanav; Kaushal, Manik; Kaur, Rubaldeep; Jeriwal, Sakshi; Pillai, Anjana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
The human temporo-mandibular joint a synovial joint is unique as it goes through a range of movements necessary for masticatory functions. Being strategically positioned between the mandible and the temporal bone, in dislocations of this joint the individual presents with a painful open mouth. Though preferred, manual reduction under local anaesthesia can be undertaken in acute dislocations. Various techniques have been advocated in global literature The oldest technique is the “Hippocratic maneuver”, that has stood the test of time. The three step procedure can be undertaken in the outpatient setup even under sedation and local anesthesia. Naval surgeon William Paul Crillon Barton, introduced the usage of bandages to hold the repositioned mandible. Lewisg modified the procedure by carrying out the three step procedure of Hippocrates in a sitting position.